2001
DOI: 10.1136/vr.148.16.497
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonographic appearance of the superficial supramammary lymph nodes in lactating dairy cattle

Abstract: The superficial supramammary lymph nodes of 54 lactating dairy cows were examined ultrasonographically with a 7.5 MHz linear transducer; each node was measured in two planes within 24 hours of recording the milk somatic cell count. In most cows, the nodes were well demarcated from the surrounding tissue. The parenchyma of the nodes ranged from hypoechoic to anechoic, with a central bright hyperechoic area, and a thin hyperechoic line surrounded the nodes. The size of the nodes varied, but their internal archit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 21 publications
0
5
0
1
Order By: Relevance
“…This finding could be attributed to the udder infection. Bradley et al (2001) found significant changes in the internal architecture of supramammary lymph node of cattle with mastitis. The dimensions of superficial inguinal lymph node were higher in infected halves compared with of isolate free halves.…”
Section: Discussionmentioning
confidence: 92%
See 3 more Smart Citations
“…This finding could be attributed to the udder infection. Bradley et al (2001) found significant changes in the internal architecture of supramammary lymph node of cattle with mastitis. The dimensions of superficial inguinal lymph node were higher in infected halves compared with of isolate free halves.…”
Section: Discussionmentioning
confidence: 92%
“…Furthermore, the significant correlations between the SCC and the ultrasonographic dimensions (length, depth and area) of the lymph node suggest such explanation. In a previous study in cattle (Bradley et al, 2001), the authors reported that the supramammary lymph node with high somatic cell count tended to be higher than those of cows with lower cell counts. In the same study, the authors found no significant correlations between any of the lymph node parameters and the cell counts.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…ise CMT pozitif örneklerden %94'ünün EC bulguları ile paralellik gösterdiği açıkla- Bradley ve ark. 33 , 54 laktasyondaki sütçü ineğin, superficial supramammary lenf yumrusunu ultra sonografik muayenesini 7.5 MHz'lik transducer ile incelemişler ve lenfin boyu ile ve SHS ve CMT ile iliş kisinde pozitif korelasyon bulamazken, yüzeysel ölçü münde CMT ile pozitif korelasyon bulmuşlardır. Lak tasyon sayısına göre gruplandırdığımız çalışmada len fin boyu ile SHS arasında rakamsal olarak pozitif ilişki bulurken, geçmişte mastitis geçiren vakalarda lenf yumrusu büyük olmasına rağmen istatistiksel bir ilişki kurulamadı.…”
Section: Baştan Ve Arkunclassified